EKSPLORASI MAKNA SIMBOLIK TARI SUFI SEBAGAI INTERVENSI KONSELING MULTIKULTURAL - Tiara, Tiara Retno Wulandari; mintarsih, widayat (AflahConsilia : Jurnal Bimbingan dan Konseling, 2025)
This study aims to explore the symbolic meaning of Sufi Dance and examine its potential as an intervention medium in multicultural counseling. Sufi Dance, as a spiritual practice in the Sufi tradition, is understood not only as a form of religious expression but also as a dynamic meditation movement that has therapeutic value for an individual's psychological balance. This article uses a literature review method, analyzing various articles, books, and academic research discussing Sufi Dance, culture-based therapy, and multicultural counseling. The results indicate that the rotating movements in Sufi Dance can produce a new state of consciousness, improve emotional regulation, and promote inner calm. Numerous literature confirms that Sufi Dance can help reduce stress, calm anxiety, support trauma processing, and provide transformative experiences through profound spiritual practices. Furthermore, Sufi values ​​such as self-surrender, divine love, and inner awareness have similarities with the concept of mindfulness, making them relevant for spiritual-based counseling interventions. The research findings indicate that Sufi Dance has the potential to be a multicultural counseling intervention by combining spiritual, emotional, and physical aspects to improve the psychological well-being of clients.